Insiden, faktor risiko, dan mortalitas rabies di Indonesia: A systematic literature review - Regina Kezia Wantania; Angela Fitriani Clementine Kalesaran; Eva Mariane Mantjoro (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Rabies is a zoonotic disease that remains a public health problem in Indonesia, with a high mortality rate, despite being preventable through vaccination and post-exposure care. Indonesia is a rabies-endemic country with a high bite rate from rabies-carrying animals, low animal vaccination coverage, delayed post-exposure prophylaxis (PEP), and a lack of public awareness, all of which contribute to the increased risk of death. Purpose: To conduct a systematic review of the incidence, risk factors, and mortality rates of rabies in Indonesia. Method: This systematic literature review (SLR) study used the PRISMA guidelines and the PICOS approach. The literature search was conducted from Google Scholar, PubMed/MEDLINE, and ScienceDirect databases for the period 2015-2025. Inclusion criteria included a cross-sectional design, Indonesian and English versions, and full-text access. Of the 4,344 articles searched, only 8 met the inclusion criteria and were reviewed. Results: The incidence of rabies in Indonesia remains high, particularly in endemic areas such as Bali, East Nusa Tenggara, and North Sulawesi, with most rabies cases caused by dog ​​bites. Key risk factors include low dog vaccination coverage, delayed or incomplete PEP, low public awareness, dense stray dog ​​populations, and limited access to health services. Rabies deaths are still reported annually, with a near 100% mortality rate after the onset of clinical symptoms, largely due to delayed treatment and a lack of public awareness of the importance of immediate action after a bite. Conclusion: Rabies in Indonesia remains a significant public health problem, with high incidence and mortality requiring serious attention. Strengthening mass vaccination programs for infected animals, improving access to and compliance with PEP, and ongoing public education are strategic steps to support the target of eliminating rabies deaths. Keywords: Incidence; Mortality; Rabies; Risk Factors.